SocPen beyond ten A process evaluation of DSWD's SocPen Program amid the COVID-19 pandemic - Albert, Jose Ramon G.; Monje, Jennifer D.; Muñoz, Mika S. (Research Paper Series)
Since 2011, the government, through the Department of Social Welfare and Development (DSWD), has been implementing the Social Pension (SocPen) Program for Indigent Senior Citizens. SocPen gives a noncontributory monthly pension of PHP 500 to qualified seniors (i.e. indigent Filipinos aged 60 and above). Budget allocation for the SocPen has increased exponentially over the years with a budget of PHP 23.4 billiion in 2021 (from an initial budget of PHP 8.71 billion at program inception). With this 2,540-percent jump in budget within 10 years, the 2021 physical target has also expanded to help 3,835,066 senior citizens identified by the Listahanan. The 2020 physical target for SocPen is nearly two-fifths (37.8%) of the country’s senior citizens. This study describes SocPen’s design and current implementation processes in the wake of the coronavirus disease 2019 pandemic, as well as attempts to increase beneficiaries’ financial assistance and coverage. It also investigates the recent experience of DSWD with the Social Amelioration Program. While overall, the program is well-intentioned and welcomed by seniors, and despite the improvements taken in response to criticisms of several external evaluations, implementation deficits persist. These issues need to be addressed, especially as the SocPen is one of the government’s largest social protection programs and has the potential to impact the lives of elderly indigent beneficiaries significantly.